Directionality of metal-induced crystallization and layer exchange in amorphous carbon/nickel thin film stacks. (15th April 2020) - Janke, Daniel; Munnik, Frans; Julin, Jaakko; Hübner, René; Grenzer, Jörg; Wüstefeld, Christina; Gemming, Sibylle; Rafaja, David; Krause, Matthias
Abstract: In thin amorphous carbon (a-C) films being in contact with a thin nickel layer, metal-induced crystallization and layer exchange (LE) occur at temperatures lower than 700 °C. Analysis of thin film stacks with different architectures (a-C/Ni, Ni/a-C and Ni/a-C/Ni) by means of ion beam analysis, Raman spectroscopy, X-ray diffraction and transmission electron microscopy revealed that the degree of LE and the structural quality of the crystallized carbon layers depend on the initial layer sequence. A LE degree of approx. 93% was found for Ni/a-C bilayers, where graphenic layers formed on the Ni surface, whereas in a-C/Ni bilayers only 83% of carbon was transferred from the surface towards the fused silica substrate. The diffusion of carbon in the outward direction produces turbostratic carbon with basal planes oriented parallel to the Ni surface, while for the inward direction planar and curved turbostratic structures coexist. The crystallization and the LE are driven by the crystallization energy of a-C. The LE is mediated by the wetting of the Ni grain boundaries by carbon. The directionality of the LE was explained primarily by the difference in the surface and interface energies in the a-C/Ni and Ni/a-C stacks that were obtained from thermodynamic considerations. Graphical abstract: Image 1